Copper-catalyzed oxidative [2+2+1] annulation of 1, n-enynes with α-carbonyl alkyl bromides through C–Br/C–H functionalization. Issue 16 (29th January 2016) - Hu, Ming; Song, Ren-Jie; Ouyang, Xuan-Hui; Tan, Fang-Lin; Wei, Wen-Ting; Li, Jin-Heng
Abstract : The Cu-catalyzed oxidative [2+2+1] annulation of 1, n -enynes ( n = 6, 7) with α-carbonyl alkyl bromides through C–Br/C–H functionalization has been developed. Abstract : The Cu-catalyzed oxidative [2+2+1] annulation of 1, n -enynes ( n = 6, 7) with α-carbonyl alkyl bromides through C–Br/C–H functionalization has been developed. Using Ag2 CO3 / tert -butyl hydroperoxide (TBHP) as co-oxidants, α-carbonyl alkyl bromides provide two bonds, the α-C(sp 3 )–Br bonds and the α-C(sp 3 )–H bonds, to cyclize with the 1, n -enynes and Cu(MeCN)4 PF6, thus forming three new C–C bonds and two rings in a single reaction.